Oral microbiota interactions with titanium implants: A pilot in-vivo and in-vitro study on the impact of peri-implantitis - Priyadharshini Sekar; Zuha Rizvi; Nizam Abdullah; A. R. Samsudin; Waad Kheder (PLoS ONE, 2025)
Introduction Dental implant therapy is a reliable approach for restoring missing teeth, offering functional and aesthetic benefits in suitable clinical cases. However, there is still a 1.9–11% implant failure rate globally. Oral microbiota plays a significant role in implant failure and peri-implant infections. Hence the impact of oral microbiota on titanium dental implants, particularly in the context of dysbiosis and peri-implant diseases, was investigated by in-vivo and in-vitro methods in this study. Materials and Methods This pilot study aimed to investigate the role of oral microbiota in peri-implant diseases associated with titanium implants. For the in-vivo study, oral microbiota was collected from titanium and hydroxyapatite (tooth-mimicking) discs placed in a custom-made intra-oral device worn by four healthy subjects. Biofilm formation, pathobionts, and bacterial diversity were assessed using DAPI staining, qPCR, and next generation sequencing (NGS)-16S rRNA sequencing. For the in-vitro study scanning electron microscopy was employed to examine the effect of oral pathogens on titanium implants. Results The study found enhanced biofilm formation on titanium implants compared to controls (p < 0.0002). Systematic colonization by Streptococcus oralis , Actinomyces naeslundii , Veillonella parvula , Fusobacterium nucleatum , Porphyromonas gingivalis , and Aggregatibacter actinomycetemcomitans was observed. An abundance of Firmicutes and Bacteroidetes, with a decrease in Proteobacteria on titanium implants was observed by NGS. SEM showed corrosion and damage to titanium implants caused by oral pathogens. Conclusion The results demonstrate that the use of titanium-based dental implants promotes oral microbiota dysbiosis, tipping the scale towards oral pathogens, which in turn contributes to the damage of the titanium implant surface. Increased biofilm formation of periodontal pathogens and microbial dysbiosis may play a role in implant failure and peri-implant diseases.